Utilização de aditivos na silagem de capim tanzânia - Melo, Maria Julia Araújo Feitosa (2015)
Various additives have been used to minimize the negative effects during the fermentation process, including Lactobacillus buchneri and / or nutritional additives such as corn meal, dry molasses, urea and lime for the purpose of improving the nutritional value and aerobic stability silages. Thus, the present study was aimed at the use of additives in silage Tanzania, they were mounted two experiments. In the first study aimed to analyze the chemical composition of grass silage Tanzania treated with different additives. The treatments were: Tanzania grass silage without additive (SSA); silage with 15% corn meal (SFM); silage with 15% molasses powder (EMS); silage inoculant based on Lactobacillus buchneri (SLB); silage additives Association: 7.5% of corn meal, 5% molasses powder, 1.1% urea, 1.1% limestone, 0.30% crushed annatto seeds and inoculant (SA1); silage additives Association: 10% of corn meal; 2.93% powdered molasses, 1.1% urea, 0.65% limestone, 0.32% of annatto seeds and inoculant (SA2). Arranged in a randomized experimental design with five replications. The content of DM (dry matter), NFC (non fibrous carbohydrate), DMS (dry matter digestibility) and TDN (total digestible nutrient) were higher in silages with additives. Silages containing additives SA1 and SA2 associations achieved the largest reductions in NDF and ADF fractions. The additives influenced the ATT where EMS had a higher acidity and lower the SLB. The associations of additives have positive synergistic effect to reduce NDF and ADF, improve NDT end of silage. The second trial was conducted to evaluate the aerobic stability of silage Tanzania treated with chemical and biological additives. The treatments were: silage without additive Tanzania (SSA); silage with 15% corn meal (SFM); silage 15% molasses (EMS); silage 2.17% urea (SUR): silage 2.17% limestone (SCA); Lactobacillus buchneri (SLB); silage Association SA1 additives: 7.5% corn flour, 5% molasses powder, 1.1% urea, 1.1% limestone, 0.30% annatto seeds; silage additives association SA2 (same proportion of SA1 over the inclusion of SLB); silage additives association SA3: 10% corn meal; 2.93% molasses powder, 1.1% urea, 0.65% limestone, 0.32% of annatto seeds; silage Association SA4 additives (same proportion of SA3 over the inclusion of SLB). he use of additives reduced the losses by effluent and gases. There was variation in dry matter values were higher in treated silages. PH results showed the interaction between treatments having desirable initial values. The breakdown of stability occurred 72, 84, 96 and 96 hours after opening the silos for SSA, SME, SLB and SA4, respectively. The combination of additives provides positive synergy and promotes greater resistance to aerobic deterioration of silage.